Unraveling stress-induced metabolic pathways in aquatic species for sustainable aquaculture practice - Turakulov, Rustam; Hossei, Rami Ryad; Zulaykho Ikromjon kizi, Abdurakhimova; Kumar, Mani Raja; Kashyap, Lakhan Lal (International Journal of Aquatic Research and Environmental Studies, 2025)
Maintaining the physiological well-being of farmed aquaculture species is crucial for their long-term sustainability and profitability, especially under diverse environmental and operational constraints. This study focuses on the stress-related metabolic pathways impacting the growth, immune function, and survival of fish and crustacean aquaculture species, with metabolomics and systems biology providing the foundational tools. With the Metabolic Stress Pathway Analysis (MSPA) methodology, we studied the oxidative stress, hyperthermia, and hypoxia response frameworks. The MSPA integrates stress metabolomics and machine learning for pathway enrichment to discover biomarkers of stress and adaptive response signatures. Stress adaptation revolves around changes to energy pathways, amino acid metabolism, and the systems of reactive oxygen species. Predictive network analysis identifies resilient and feed-efficient fish regulatory hubs. This work is of primary importance in developing stress-sustainable aquaculture management frameworks and in developing economically viable and environmentally sustainable species under stress. The trade contemplated on the molecular reflections and their applications for aquaculture should be a springboard for developing precision health systems for monitoring aquaculture species and for aquaculture systems of high resource use efficiency.